Role of vitamin C and rectal indomethacin in preventing and alleviating post-endoscopic retrograde cholangiopancreatography pancreatitis: a clinical study - Amir Sadeghi; Rana Jafari-Moghaddam; Sara Ataei; Mahboobe Asadiafrooz; Mohammad Abbasinazari (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims This study aimed to determine whether vitamin C in addition to indomethacin decreases the occurrence and severity of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) occurrence and severity. Methods This randomized clinical trial included patients undergoing ERCP. The participants were administered either rectal indomethacin (100 mg) plus an injection of vitamin C (500 mg) or rectal indomethacin (100 mg) alone just before ERCP. The primary outcomes were PEP occurrence and severity. The secondary amylase and lipase levels were determined after 24 hours. Results A total of 344 patients completed the study. Based on intention-to-treat analysis, the PEP rates were 9.9% for indomethacin plus vitamin C plus indomethacin and 15.7% for indomethacin alone. Regarding the per-protocol analysis, the PEP rates were 9.7% and 15.7% in the combination and indomethacin arms, respectively. There was a remarkable difference between the two arms in PEP occurrence and severity on intention-to-treat and per-protocol analyses (p=0.034 and p=0.031, respectively). The post-ERCP lipase and amylase concentrations were lower in the combination arm than in the indomethacin alone arm (p=0.034 and p=0.029, respectively). Conclusions Vitamin C injection in addition to rectal indomethacin reduced PEP occurrence and severity.